PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM LAYANAN ADMINISTRASI AKADEMIK TERHADAP PENINGKATAN KINERJA DI SMA NEGERI KOTA JAMBI - Idrus, Ali (Program Magister Teknologi Pendidikan Universitas Jambi, 2014)
The purpose of this research is to explain the performance of the school institution that uses the management of academic information system (AIS management effectiveness, Culture ICT, ICT facilities and the quality of the Human resources) on the performance of the institution; partially include: effectiveness of management on the performance of Academic Information Systems agencies; ICT culture on the performance of the institution; availability of ICT facilities for the performance of the institution; and quality of human resources Academic Information System on the performance of the institution. This study used a descriptive analytical method. The data used are primary and secondary data obtained through surveys and documentation. The data analysis techniques-quantitative analysis examines the effectiveness of management, ICT culture, availability of ICT facilities, and quality of human resources for the school's performance and its impact on the academic achievement of students in schools in the city of Jambi, as object of study. Keyword: Information communication and technology (ICT), effectiveness, school performance